2016
DOI: 10.1038/ncomms11775
|View full text |Cite
|
Sign up to set email alerts
|

LRP6 acts as a scaffold protein in cardiac gap junction assembly

Abstract: Low-density lipoprotein receptor-related protein 6 (LRP6) is a Wnt co-receptor in the canonical Wnt/β-catenin signalling. Here, we report the scaffold function of LRP6 in gap junction formation of cardiomyocytes. Cardiac LRP6 is spatially restricted to intercalated discs and binds to gap junction protein connexin 43 (Cx43). A deficiency in LRP6 disrupts Cx43 gap junction formation and thereby impairs the cell-to-cell coupling, which is independent of Wnt/β-catenin signalling. The defect in Cx43 gap junction re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…Here we have studied the biogenesis of Low-density lipoprotein Receptor-related Protein 6 (LRP6), a key component of the canonical Wnt signaling pathway, which has been associated with many human pathologies including cancer, osteoporosis and metabolic diseases (Joiner et al, 2013), but also involved in the formation of gap junctions in cardiomyocytes (Li et al, 2016). LRP6 is a type I membrane protein composed of a large extracellular domain containing multiple ß-propeller and EGF-like domains (MacDonald et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Here we have studied the biogenesis of Low-density lipoprotein Receptor-related Protein 6 (LRP6), a key component of the canonical Wnt signaling pathway, which has been associated with many human pathologies including cancer, osteoporosis and metabolic diseases (Joiner et al, 2013), but also involved in the formation of gap junctions in cardiomyocytes (Li et al, 2016). LRP6 is a type I membrane protein composed of a large extracellular domain containing multiple ß-propeller and EGF-like domains (MacDonald et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we observed that LRP6 interacted with N‐cadherin, γ‐catenin, β‐catenin and Cx43, but not with desmoplakin. Li et al reported that LRP6 interacts with Cx43, and LRP6 deficiency causes Cx43 degradation (Li et al, ). However, only few studies have reported LRP6 interaction with other ID proteins.…”
Section: Discussionmentioning
confidence: 99%
“…LRP6 is widely expressed in human and mouse tissues, including the cardiovascular system. Li et al () reported that LRP6 acts as a scaffold protein regulating connexin 43 (Cx43) expression. It was recently found that cardiac‐specific LRP6 knockout induces lethal cardiac dysfunction by activation of dynamin‐related protein 1 (Drp1) (Chen, Li, Wang, et al, ); abnormal structure of the intercalated disk (ID) in LRP6‐deficient hearts was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Cx43 in cultured neonatal myocytes (as in intact neonatal ventricular myocardium) is distributed around the entire cell perimeter rather than being located at the poles of the cells in IDs in adult myocytes (50)(51)(52). It is plausible that Cdon might regulate the localization of Cx43 through a Wnt-independent pathway, such as N-cadherin or LRP6, because Cdon is localized at the ID and directly interacts with N-cadherin (53) and LRP6 (28), both of which are implicated in proper localization of Cx43 (54)(55)(56)(57). Regardless, the results presented here provide direct evidence of a functional role for Cdon in the control of Cx43 expression and its localization to the ID at the site of end-to-end contacts between cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%